Implementation of Mortgage Rights on the Position of Creditors of Second Mortgage Holders in the Application for Auction Submission - Rianto, Fera Puspita; Suriaatmadja, Toto Tohir; Jamilah, Lina (Journal La Sociale, 2024)
The binding of credit collateral with mortgage rights can be bound by several creditors with more than one mortgage. If the debtor is in default, only the creditor holding the first rank of mortgage rights can submit the auction, as stated in Law Number 4 of 1996 concerning Mortgage Rights. At the time of the debtor's default, the binding of the first-ranked mortgage has been released by the creditor of the first mortgage holder, the second mortgage holder applies for a mortgage auction and is rejected based on the law. The purpose of this research is to find regulations that provide justice to creditors of second lien holders. Implementation based on the principle of justice to the position of the creditor of the second lien holder in the application for submission of the auction. The research method used in this research uses a normative juridical approach, descriptive analysis and prescriptive analysis specifications with secondary and primary data types, data collection through interviews and qualitative juridical analysis methods, comparative heurmeneutic data that interpret and understand the intent of the regulatory text. The results of this study, as well as updates to previous research, the application of the Mortgage Rights regulation has not been based on the principle of justice, based on the value of justice, it should be that if the debtor is in default, the holder of the mortgage right has the right to sell the object of the mortgage right on its own power through a public auction with the first mortgage right holder having the first right to take repayment of its debt from the proceeds of the sale.